TAMPILAN BIREFRINGENCE PADA GANGGUAN PEMBENGKOKAN SERAT OPTIK KOMERSIAL - Velia Veriyanti; Saktioto Saktioto (Universitas Riau, 2020)
Optical fiber components are increasingly growing in the telecommunication technology with various forms to facilitate effective and stable communication. However, the output signal of optical fiber is still experiencing interference, bending power loss n and dispersion, such as birefringence. To minimize the interference, this paper investigates birefringence profile on the aspect of disturbance and geometrical parameters for commercial single-mode optical fiber (SMF) through OptiFiber simulation. This simulation build the model of several SMFs, namely SMF-28, SMF-28e, SMF-28e +, SMF-28e + LL, and SMF-28 ULL which have different refractive index for core and cladding, but their radii are fixed for each wavelength source of 1310nm and 1550nm. The impact of interference on optical fiber can be understood from birefringence model of its bending radius to power loss and wavelength. The highest loss occurred at SMF-28 fiber of 0.012dB / km with a radius of 0.020m for wavelength of 1310nm and bending loss at wavelength of 1550nm was 31.96dB / km at radius of 0.02m. This finding shows that magnitude of normalized frequency strongly determines the effectiveness and stability of optical fibers.